Assignment integration in order to achieve the successful studio-based education (An Idea Implementation of Integrated Architecture Experiential Learning) - Yaseri D. Apritasari; Doni Fireza (IPTEK Journal of Proceedings Series, 2017)
The formal architecture undergraduate degree (S1) is determined by taking total 144 credits, in 8 semesters (4 years). After he/she graduated and earn the B.Arch, to become a professional architect one must take 1-2 year’s professional diploma including internship in one architectural bureau. All this limitations may cause several strategies such as a curriculum adjustment in order to meet all the teaching materials needed. Those strategies includes; eliminating some subjects that considered not necessary, decreasing the teaching materials content in order to create lesser credits so more subjects may be added into the curriculum, or merging some subjects into a new subject and adding more credits into it. This condition affecting the learning objective of the new subject cannot be achieved optimally. Seeing this tendency, an idea has emerged by integrating some of the subjects’ assignments into one comprehensive assignment. This concept is derived into scenarios that a student will undergo a one big assignment containing materials from several subjects, and the scoring phase will be examined from several subjects’ point of views. This paper will discuss the effectiveness of architecture subject assignment integration, in this case the architecture design studio as the core of architecture education with other supporting subjects including the theoretical subjects, to achieve architecture education’s target and objective. Methodology of research used is qualitative research through observation methods: (1) Condition of the studio assignments with other supporting subjects (theory and skill) assignments that can be integrated, (2) Strategy to achieve the learning objective target through the integration of the studio assignments with other subjects' assignments, (3), Advantage and disadvantage of the assignments’ integration scenario. Hopefully the result of the integration of the studio assignments with other subject's assignments can achieve the successful architecture education, effective, target fulfilled, and optimized